Functions of multidimensional marketing strategy - Rohollah Bagheri (مطالعات مدیریت راهبردی, 2021)
Aim and Introduction: The impact of organizations on the intention to repurchase consumers in today's highly competitive markets is one of the main issues and challenges for organizations that companies must recognize and personalize the needs of customers in order to survive and be active in investing in customer relations to  act. The purpose of this study is to investigate the effect of multidisciplinary marketing strategy including relationship marketing and personalization on consumers' intention to repurchase through appreciation. Data were collected by distributing 390 questionnaires among customers of luxury restaurants in Mashhad. The relationship between the variables was investigated through structural equation modeling with the help of AMOS software. The results show that relationship marketing and personalization affect customers' repurchase intent; In addition, relationship marketing and personalization have a positive and significant effect on appreciation. Also, the role of appreciation mediation in the relationship between relationship marketing and personalization with the intention of repurchasing customers was confirmed.Competition in the restaurant industry is growing, especially among luxury restaurant owners, and restaurants that used to have a good market share are now worried about losing customers as a result of their market share. However, with increasing competition among restaurant owners, success in this area is no longer easily possible, because customers, as in the past, do not just go to restaurants to eat, but to have the best service to have a good time. As the number of restaurants increases, more options will be available to customers, and in these circumstances, expecting customer loyalty is a mistake. Restaurant owners expect to have an impact on customer reuse for the huge costs they incur in setting up stylish and luxurious restaurants to leave beautiful memories in the minds of their customers. So in today's era, in order to influence customer purchases, multifaceted attention and impressing customers using several marketing methods is a way to success. Among the issues mentioned influencing customers, we can mention relational marketing, personalization and appreciation, which have been widely considered by researchers in recent years. The city of Mashhad, as the largest guest city in Iran, receives about twenty million guests annually, while the population of the city as the second largest and most populous city in Iran makes it a place with high potential for the construction and operation of the hospitality industry. Therefore, the necessity of conducting research can be expressed as follows: The importance of designing practical solutions to influence consumers' intention to repurchase in the food industry is increasingly felt.2. Losing customers entails huge costs for the organization, and in addition, customers who leave organizations turn to competing organizations. 3. Given that most studies on the use of several marketing methods simultaneously and its effect on repurchase intention Consumerism has taken place in developed countries and the food industry has been neglected. To better understand this phenomenon, research is needed according to the cultural conditions of Iranian society.  Methodology: This research is applied in terms of purpose and survey-analytical in terms of method. Standard measures of previous studies were used to measure the variables. Questionnaire questions in relational marketing variable 3 questions from Mishra studies (2016), in the field of appreciation 3 questions from research conducted by (Hassan et al., 2015), 5 questions about personalization from studies (Hassan et al., 2014) and finally Three questions were selected to measure repurchase intention taken from studies (Palmiter et al., 2009). The validity of the questionnaire constructs was also evaluated using factor analysis technique. Customers of luxury restaurants in Mashhad who have used the services of these restaurants more than twice make up the statistical population of this study. Cochran's formula was used to determine the sample size for the unknown community (384 people). Since some of the questionnaires were not returned, 450 non-randomly available questionnaires were distributed among the customers of these restaurants, and at the end of the follow-up, 390 of these questionnaires were returned to the researchers for analysis. In order to analyze the data, various methods of statistical analysis, such as modeling structural equations to fit the pattern of these equations using the collected data, Pearson correlation analysis has been used to calculate zero-order correlation coefficients. In this study, the features of AMOS software such as torque structure analysis and social science statistical features of SPSS software were used.Findings: In this study, seven hypotheses were formulated that were confirmed. Therefore, based on the results of research in the statistical community, it can be said that: relational marketing and personalization affect the intention to repurchase customers; In addition, relationship marketing and personalization have a positive and significant effect on appreciation. The role of gratitude mediation in the relationship between relationship marketing and personalization with the intention of repurchasing customers was also confirmed.Discussion and Conclusion: Considering the results of the research, it can be claimed that the adoption of multifaceted marketing strategies in the organization has a significant effect on increasing the impact on the intention of customers to buy restaurants in Mashhad. And by having multifaceted marketing strategies, it is possible to meet the needs of customers in different ways and achieve a satisfied customer who will show his loyalty in future purchases from the organization. Therefore, managers in the service industry remained industry. Tourism and restaurant management should be diligent in adopting multiple marketing strategies at the same time and seek to improve customer relationships by adopting multidisciplinary marketing strategies. According to the obtained results, these suggestions are that restaurant managers with strategic planning in order to create long-term bilateral relationships to instill a sense of gratitude in their customers and by training a tasteful, creative and capable force in creating verbal communication in the direction of attention to Making connections in addition to the above is achieved according to the results, restaurant managers should seek to know their customers and by hiring and training skilled people, conducting thorough marketing research to obtain customer information and personalize services for them In this way, to prove the customer's sense of attention to him in practice. Another suggestion is to use customer relationship techniques and the science of consumer behavior to influence customer repurchase intent. The application of new methods of marketing research to identify the new needs of customers and the development of a variety of services in line with these needs, as well as the use of new methods of sales, promotions, special discounts, awards and lotteries should be considered. Use trained people in the sales department in such a way that these people communicate well with customers and in line with the organization's strategy to instill in them a sense of appreciation for the customer's purchase. Other suggestions include having a suitable strategic plan for marketer research to identify the tastes and needs of customers and having an integrated marketing plan for the organization. The above seeks to create a customer-oriented appreciation so that the consumer fully understands that the organization values ​​the customer's trust and appreciates his behavior.